Quantifying and modelling the game speed outputs of English Championship soccer players - Connor, M.; Mernagh, D.; Beato, M. (Research in Sports Medicine, 2022)
This study aims to quantify and model the game-speed demands of professional soccer players competing in the English Championship league, to compare the effect of match location and to examine the effect of playing position on game-speed outputs across the season. Twenty-eight male professional soccer players were enrolled. Moving average calculations were applied to the raw GNSS (STATSports) speed data of each player`s duration matches (home=14 and away=9). Positional groups were centre-back (CB), full-back (FB), centre-midfield (CM), wing-midfield (WM) and centre-forward (CF). The maximum value across each of the moving average window durations was extracted and converted to units of metres per minute. Power-law models were fitted to all observations (R2=0.64), home only (R2=0.98), and away only (R2=0.98). No significant effects are observed in game-speed outputs when home and away games are analysed. Significant differences were seen between the following positional groups; CBvs.CF (d =-0.323), CM (d =-0.530) and FB (d =-0.350). CM displayed positive difference compared to WM (d =0.614). This study reported power-law model fitted game speed. Players` positional groups have significantly different game-speed demands, which should be considered during match analysis and training periodization. This study found that game speed is not affected by the location of the match.